A composite material for modified polyethylene trenchless pipe and a method for preparing the same
Patent Information
- Application Number
- CN202611150732.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-31
AI Technical Summary
然而,该申请文件以原生高密度聚乙烯作为唯一基体,未能实现回收高密度聚乙烯的循环利用,原料成本较高;同时,单纯依靠聚偏氟乙烯提高管材表面的耐磨性能,并不能避免非开挖拖拉施工过程中砂石、岩块等硬质颗粒对管材外壁产生的划伤和犁削磨损
1、本发明中胺醇改性HDPE能够与回收HDPE中的含氧极性基团产生氢键、极性吸附和酸碱作用,并利用HDPE主链与聚乙烯基体之间良好的相容性,在回收HDPE与原生HDPE之间起到桥接相容作用,同时有利于纳米蒙脱土分散,提高复合材料界面结合、环刚度和耐划伤性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composition technology, specifically to a modified polyethylene trenchless pipe composite material and its preparation method. Background Technology
[0002] Polyethylene (PE) pipes are widely used in water supply and drainage, power and communication protection, gas transmission, and municipal pipeline construction due to their excellent corrosion resistance, high flexibility, light weight, convenient installation and connection, high construction efficiency, and long service life. However, with the increasing density of urban roads, buildings, and underground pipelines, traditional open-cut laying methods are prone to road surface damage, traffic disruption, noise and dust pollution, and extended construction periods, thus limiting their application. Therefore, trenchless directional drilling (DDR) has gradually become an important method for urban pipeline laying and repair due to its advantages of minimal construction disturbance, high efficiency, and low impact on the ground environment. However, during DDR traction construction, the pipe needs to be pulled long distances through underground tunnels. Due to complex geological conditions, irregular borehole walls, and the presence of hard and sharp objects such as underground sand, rocks, and bulk metal, the outer wall of the polyethylene pipe is prone to scratches, wear, and localized stress concentration, which weakens the pipe's compressive and impact resistance, posing a potential risk to the safe operation of the pipeline.
[0003] To address the issues of insufficient surface wear resistance and susceptibility to scratches in trenchless engineering polyethylene pipes, patent application CN114181444A discloses a trenchless engineering polyethylene pipe comprising the following raw materials in parts by weight: 100 parts high-density polyethylene, 3-5 parts mica, 5-10 parts functional modifier, 0.5-1 part silane coupling agent, 3-5 parts color masterbatch, and 3-5 parts antioxidant masterbatch. The functional modifier is glyceryl methacrylate-activated modified polyacrylamide and polyvinylidene fluoride. This application utilizes the modification of the inner wall of the pipe with polyacrylamide to reduce the frictional resistance of water within the pipe; and utilizes polyvinylidene fluoride to improve the wear resistance of the pipe surface. However, this application uses virgin high-density polyethylene as the sole matrix, failing to achieve the recycling of high-density polyethylene, resulting in high raw material costs. Furthermore, simply relying on polyvinylidene fluoride to improve the wear resistance of the pipe surface cannot prevent scratches and plowing wear caused by hard particles such as sand and rock during trenchless towing construction. In addition, directly adding mica easily causes the agglomeration of sheet-like fillers, limiting interfacial bonding and stress transfer effects, making it difficult to balance the contradiction between ring stiffness and impact resistance.
[0004] Therefore, there is a need to provide a modified polyethylene trenchless pipe composite material and its preparation method to solve the above-mentioned technical problems. Summary of the Invention
[0005] In view of this, the present invention provides a modified polyethylene trenchless pipe composite material and its preparation method, which can improve the ring stiffness, impact resistance and wear and scratch resistance of the composite material.
[0006] To achieve the above objectives, the present invention provides a method for preparing a modified polyethylene trenchless pipe composite material, comprising the following steps:
[0007] S1. Maleic anhydride-grafted high-density polyethylene is vacuum dried, then mixed with antioxidant and 2-[2-(dimethylamino)ethoxy]ethanol under inert gas protection, discharged, and granulated to obtain amino alcohol modified HDPE. S2. The recycled high-density polyethylene crushed material is screened, washed, filtered, dried, and then premixed with amino alcohol modified HDPE and additives. It is then melt-extruded and granulated to obtain modified recycled HDPE masterbatch. S3. After vacuum drying of linear low-density polyethylene, it is premixed with maleic anhydride, vinyltrimethoxysilane and dicumyl peroxide, reacted and extruded, and granulated to obtain functionalized LLDPE. S4. High-density polyethylene, modified recycled HDPE masterbatch and functionalized LLDPE are premixed, and then dried nano-montmorillonite, zinc stearate modified wollastonite fiber and other additives are added and mixed. The mixture is then melt-extruded, granulated and vacuum-dried to obtain a modified polyethylene trenchless pipe composite material.
[0008] In this invention, the hydroxyl groups in 2-[2-(dimethylamino)ethoxy]ethanol can undergo ring-opening esterification with the anhydride groups on the side chains of maleic anhydride-grafted HDPE, thereby introducing an amino alcohol structure containing tertiary amine groups into the HDPE molecular chain, resulting in amino alcohol-modified HDPE containing polar groups such as ester groups, carboxyl groups, and tertiary amine groups. These polar groups can interact with the oxygen-containing polar groups in recycled high-density polyethylene through hydrogen bonding, polar adsorption, and acid-base association, forming an interfacial bond between the amino alcohol-modified HDPE and the recycled HDPE. Simultaneously, by pre-modifying the recycled high-density polyethylene with amino alcohol-modified HDPE, the good compatibility of its HDPE backbone with both recycled and virgin HDPE as similar polyolefins can be utilized, thus bridging the gap between the recycled and virgin HDPE, improving the interfacial bond between them, and reducing the adverse effects of the addition of recycled HDPE on the mechanical properties of the composite material. In addition, amino alcohol modified HDPE can interact with the polar sites on the surface of the subsequently added nano-montmorillonite sheets, which helps to improve the dispersibility of nano-montmorillonite in the polyethylene matrix, reduce its agglomeration, and further improve the interfacial bonding strength, ring stiffness and scratch resistance of the composite material.
[0009] In this invention, functionalized LLDPE is produced by reactive extrusion of linear low-density polyethylene, maleic anhydride, and vinyltrimethoxysilane into the LLDPE molecular chain under the initiation of dicumyl peroxide. This process introduces anhydride groups and alkoxysilane structures into the LLDPE molecular chain, resulting in a functionalized LLDPE with both flexible LLDPE segments and polar functional groups. The flexible LLDPE segments can form a flexible phase within the high-density polyethylene matrix, reducing the risk of brittle cracking and improving the impact resistance of the composite material. The anhydride groups and alkoxysilane structures can interact with the oxygen-containing polar groups in modified recycled HDPE and the polar sites on the surfaces of nano-montmorillonite and zinc stearate-modified wollastonite fibers, thereby improving the interfacial compatibility between the polyethylene matrix and the inorganic reinforcing components, enhancing the dispersion stability of nano-montmorillonite and modified wollastonite fibers in the polyethylene system, and reducing inorganic filler agglomeration and interfacial debonding.
[0010] In this invention, nano-montmorillonite and zinc stearate-modified wollastonite fibers are used together as inorganic reinforcing components. Nano-montmorillonite has a lamellar structure, which can restrict the slippage and creep of polyethylene molecular chains; wollastonite fibers have a needle-like rigid structure, which can form a supporting skeleton in the matrix and transfer external loads. The synergistic effect of the two can disperse stress and hinder crack propagation, thereby improving the ring stiffness of the composite material while maintaining good impact resistance, making it more suitable for trenchless pipes to meet the requirements of external pressure and deformation resistance. Simultaneously, nano-montmorillonite and wollastonite fibers can improve the material surface's resistance to friction, cutting, and ploughing; the zinc stearate modification of wollastonite fibers can improve the compatibility and dispersibility between wollastonite fibers and the polyethylene matrix, and has a certain lubricating effect, thus synergistically improving the wear resistance and scratch resistance of the composite material with functionalized LLDPE, reducing the risk of wear, scratches, and groove damage to the outer wall of the pipe during trenchless towing construction.
[0011] Optionally, in step S1, maleic anhydride-grafted high-density polyethylene is vacuum dried at 75-85°C for 8-12 hours, then added to a mixer with an antioxidant, heated to 160-165°C under nitrogen protection, and mixed at 50-70 r / min for 2-4 minutes. Then, 2-[2-(dimethylamino)ethoxy]ethanol is added and mixed at 160-165°C and 50-70 r / min for 10-12 minutes. The mixture is then discharged, cooled, and pelletized to obtain amino alcohol-modified HDPE.
[0012] Optionally, the amino alcohol modified HDPE comprises the following raw materials in parts by weight: 6-7.5 parts maleic anhydride-grafted high-density polyethylene, 0.02-0.025 parts antioxidant, and 0.15-0.25 parts 2-[2-(dimethylamino)ethoxy]ethanol.
[0013] Preferably, the antioxidant is antioxidant 1010.
[0014] Optionally, in step S2, the recycled high-density polyethylene (HDPE) crushed material is screened, placed in a sodium carbonate aqueous solution, washed at 45-55°C for 20-30 minutes, washed with deionized water for 20-30 minutes, filtered, dried at 80°C for 8 hours, then added with amino alcohol modified HDPE and additives and premixed at 800-1000 r / min for 5-10 minutes, then added to a twin-screw extruder and melt-extruded at 170-190°C, cooled, and pelletized to obtain modified recycled HDPE masterbatch; the mass ratio of the recycled HDPE crushed material to the amino alcohol modified HDPE is 50:(2-4).
[0015] In this invention, the recycled high-density polyethylene (HDPE) crushed material is first cleaned, which helps to remove mud, sand, oil, and acidic impurities from the surface of the recycled HDPE, thereby improving the purity of the masterbatch and the processing stability.
[0016] Optionally, the concentration of the sodium carbonate aqueous solution is 1 wt%; the additives include 0.1-0.2 parts of antioxidant 1010, 0.1-0.2 parts of antioxidant 168 and 0.2-0.4 parts of polyethylene wax.
[0017] Optionally, in step S3, linear low-density polyethylene is vacuum dried at 75~80℃ for 6~8h, then premixed with maleic anhydride, vinyltrimethoxysilane and dicumyl peroxide for 20~30min, added to a twin-screw extruder, reacted and extruded at 160~175℃, cooled and pelletized to obtain functionalized LLDPE.
[0018] This invention first vacuum-dries linear low-density polyethylene, which helps remove residual moisture from the surface and interior of the raw material, reduces the generation of defects such as maleic anhydride hydrolysis, premature hydrolysis and condensation of vinyltrimethoxysilane, and bubbles and pores during extrusion, thereby improving the reaction stability and interface modification effect of functionalized LLDPE.
[0019] Optionally, the functionalized LLDPE comprises the following raw materials in parts by weight: 8-12 parts linear low-density polyethylene, 0.15-0.2 parts maleic anhydride, 0.05-0.1 parts vinyltrimethoxysilane, and 0.01-0.015 parts dicumyl peroxide.
[0020] This invention employs maleic anhydride and vinyltrimethoxysilane co-grafting of linear low-density polyethylene (LLDPE). Under the initiation of dicumyl peroxide, the LLDPE molecular chain generates free radical active sites, allowing maleic anhydride and vinyltrimethoxysilane to be grafted onto the LLDPE molecular chain, resulting in a functionalized LLDPE that combines flexible polyethylene segments, anhydride polar groups, and alkoxysilane structures.
[0021] Optionally, the zinc stearate modified wollastonite fiber is obtained by drying wollastonite fiber at 100~110℃ for 2~4h, cooling it to room temperature, adding zinc stearate, mixing and stirring at 1000r / min for 15~30min, and then transferring it to a ball mill jar and ball milling at 100r / min for 20~30min; the mass ratio of wollastonite fiber to zinc stearate is 10:(0.2~0.4). The dried nano-montmorillonite is obtained by drying nano-montmorillonite at 90~110℃ for 2~4h and then cooling it to room temperature.
[0022] This invention utilizes the shearing, collision, and friction effects during high-speed mixing and ball milling to promote the adsorption and coating of zinc stearate on the surface of wollastonite fibers, thereby reducing the surface polarity of wollastonite fibers and improving their hydrophobicity and compatibility with the polyethylene matrix. At the same time, zinc stearate also has a certain lubricating effect, which can improve the flowability of the composite material during melt processing and the smoothness of the extruded surface, and reduce the risk of surface wear on the outer wall of the pipe during dragging construction.
[0023] Drying nano-montmorillonite can remove adsorbed water on its surface and free water between layers, reduce bubbles, pores and agglomeration during melt extrusion, improve its dispersibility and interfacial bonding stability in polyethylene matrix, and thus give fuller play to the lamellar reinforcement and scratch resistance of nano-montmorillonite.
[0024] Optionally, in step S4, high-density polyethylene, modified recycled HDPE masterbatch, and functionalized LLDPE are premixed at 800 r / min for 5-8 min, then dried nano-montmorillonite, zinc stearate modified wollastonite fiber, and other additives are added and mixed at 1000 r / min for 8-10 min. The mixture is then melt-extruded at 170-190°C, cooled, pelletized, and vacuum-dried at 70°C for 5 h to obtain a modified polyethylene trenchless pipe composite material. The other additives are 0.2-0.3 parts of antioxidant 1010, 0.2-0.3 parts of antioxidant 168, and 0.5-0.7 parts of polyethylene wax.
[0025] The present invention also provides a modified polyethylene trenchless pipe composite material, comprising the following raw materials in parts by weight: 50-60 parts high-density polyethylene, 25-30 parts modified recycled HDPE masterbatch, 8-10 parts functionalized LLDPE, 1.5-2 parts dried nano-montmorillonite, 7-10 parts zinc stearate modified wollastonite fiber, and 0.9-1.3 parts other additives.
[0026] This invention, by limiting the proportions of high-density polyethylene, modified recycled HDPE masterbatch, functionalized LLDPE, nano-montmorillonite, modified wollastonite fiber, and additives, enables each component to achieve a synergistic effect in terms of matrix strength, interfacial compatibility, flexibility and toughness, and inorganic reinforcement. This not only improves the stability of recycled material utilization but also takes into account ring stiffness, impact resistance, and wear and scratch resistance, making the composite material more suitable for trenchless polyethylene pipes.
[0027] The above-described technical solution of the present invention has at least the following beneficial effects: 1. In this invention, the amino alcohol modified HDPE can generate hydrogen bonds, polar adsorption and acid-base interactions with the oxygen-containing polar groups in recycled HDPE. It also utilizes the good compatibility between the HDPE main chain and the polyethylene matrix to play a bridging compatibility role between recycled HDPE and virgin HDPE. At the same time, it is beneficial to the dispersion of nano-montmorillonite and improves the interfacial bonding, ring stiffness and scratch resistance of the composite material.
[0028] 2. In this invention, the anhydride-alkoxysilane functionalized LLDPE contains flexible LLDPE segments, anhydride groups, and alkoxysilane structures. The flexible segments can form a flexible phase in the HDPE matrix, improving impact resistance; the anhydride and alkoxysilane structures can interact with the polar sites on the surfaces of modified recycled HDPE, nano-montmorillonite, and modified wollastonite fibers, improving the dispersibility of inorganic components and reducing agglomeration and interfacial debinding.
[0029] 3. In this invention, the layered structure of nano-montmorillonite can restrict the slippage and creep of polyethylene molecular chains, and the needle-like rigid structure of wollastonite fiber can form a supporting skeleton and transfer load. The two work together to improve the ring stiffness, impact resistance and wear and scratch resistance of the composite material. At the same time, zinc stearate modification can improve the compatibility and dispersibility of wollastonite fiber with polyethylene matrix and impart a certain lubricating effect. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are some embodiments of the present invention, and all other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0031] Example 1 Ten parts of wollastonite fiber were dried at 105℃ for 3 hours, cooled to room temperature, and then 0.3 parts of zinc stearate were added. The mixture was stirred at 1000 r / min for 25 min, and then transferred to a ball mill jar and ball milled at 100 r / min for 25 min to obtain zinc stearate modified wollastonite fiber.
[0032] Seven parts of maleic anhydride-grafted high-density polyethylene were vacuum dried at 80°C for 10 hours. Then, 0.023 parts of antioxidant 1010 were added to a mixer and heated to 163°C under nitrogen protection. The mixture was then kneaded at 60 r / min for 3 minutes. Next, 0.2 parts of 2-[2-(dimethylamino)ethoxy]ethanol (CAS No.: 1704-62-7) were added and the mixture was kneaded at 163°C and 60 r / min for 11 minutes. The mixture was then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
[0033] Fifty parts of recycled high-density polyethylene (HDPE) crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 50°C for 25 min, washed with deionized water for 25 min, filtered, dried at 80°C for 8 h, and then 3 parts of amino alcohol modified HDPE, 0.15 parts of antioxidant 1010, 0.15 parts of antioxidant 168 and 0.3 parts of polyethylene wax were added and premixed at 900 r / min for 8 min. The mixture was then fed into a twin-screw extruder and melt-extruded at 180°C. After cooling and pelletizing, modified recycled HDPE masterbatch was obtained.
[0034] Ten parts of linear low-density polyethylene were vacuum dried at 78°C for 7 hours, and then premixed with 0.18 parts of maleic anhydride, 0.08 parts of vinyltrimethoxysilane, and 0.012 parts of dicumyl peroxide for 25 minutes. The mixture was then added to a twin-screw extruder and reacted and extruded at 165°C. After cooling and pelletizing, functionalized LLDPE was obtained.
[0035] 2.5 parts of nano-montmorillonite (CAS No.: 1318-93-0) were dried at 100℃ for 3 hours and cooled to room temperature to obtain dried nano-montmorillonite. 55 parts of high-density polyethylene (PE100), 28 parts of modified recycled HDPE masterbatch, and 9 parts of functionalized LLDPE were premixed at 800 r / min for 6 minutes. Then, 1.8 parts of dried nano-montmorillonite, 9 parts of zinc stearate modified wollastonite fiber, 0.25 parts of antioxidant 1010, 0.25 parts of antioxidant 168, and 0.6 parts of polyethylene wax were added and mixed at 1000 r / min for 9 minutes. The mixture was then melt-extruded at 180℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 hours to obtain a modified polyethylene trenchless pipe composite material.
[0036] Example 2 Ten parts of wollastonite fiber were dried at 100℃ for 2 hours, cooled to room temperature, and then 0.2 parts of zinc stearate were added. The mixture was stirred at 1000 r / min for 15 min, and then transferred to a ball mill jar and ball milled at 100 r / min for 20 min to obtain zinc stearate modified wollastonite fiber.
[0037] Six parts of maleic anhydride-grafted high-density polyethylene were vacuum dried at 75°C for 8 hours. Then, 0.02 parts of antioxidant 1010 were added to a mixer and heated to 160°C under nitrogen protection. The mixture was then mixed at 50 r / min for 2 minutes. Next, 0.15 parts of 2-[2-(dimethylamino)ethoxy]ethanol (CAS No.: 1704-62-7) were added and the mixture was further mixed at 160°C and 50 r / min for 10 minutes. The mixture was then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
[0038] Fifty parts of recycled high-density polyethylene (HDPE) crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 45°C for 20 min, washed with deionized water for 20 min, filtered, dried at 80°C for 8 h, and then 2 parts of amino alcohol modified HDPE, 0.1 parts of antioxidant 1010, 0.1 parts of antioxidant 168 and 0.2 parts of polyethylene wax were added and premixed at 800 r / min for 5 min. The mixture was then fed into a twin-screw extruder and melt-extruded at 170°C. After cooling and pelletizing, modified recycled HDPE masterbatch was obtained.
[0039] Eight parts of linear low-density polyethylene were vacuum dried at 75°C for 6 hours, then premixed with 0.15 parts of maleic anhydride, 0.05 parts of vinyltrimethoxysilane, and 0.01 parts of dicumyl peroxide for 20 minutes. The mixture was then added to a twin-screw extruder and reacted and extruded at 160°C. After cooling and pelletizing, functionalized LLDPE was obtained.
[0040] Two parts of nano-montmorillonite (CAS No.: 1318-93-0) were dried at 90℃ for 2 hours and cooled to room temperature to obtain dried nano-montmorillonite. 50 parts of high-density polyethylene (PE100), 25 parts of modified recycled HDPE masterbatch, and 8 parts of functionalized LLDPE were premixed at 800 r / min for 5 minutes. Then, 1.5 parts of dried nano-montmorillonite, 7 parts of zinc stearate modified wollastonite fiber, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.5 parts of polyethylene wax were added and mixed at 1000 r / min for 8 minutes. The mixture was then melt-extruded at 170℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 hours to obtain a modified polyethylene trenchless pipe composite material.
[0041] Example 3 Ten parts of wollastonite fiber were dried at 103℃ for 2.5h, cooled to room temperature, and then 0.25 parts of zinc stearate were added. The mixture was stirred at 1000r / min for 18min, and then transferred to a ball mill jar and ball milled at 100r / min for 23min to obtain zinc stearate modified wollastonite fiber.
[0042] 6.3 parts of maleic anhydride-grafted high-density polyethylene were vacuum dried at 78°C for 9 hours, and then added to a mixer with 0.021 parts of antioxidant 1010. The mixture was heated to 162°C under nitrogen protection and mixed at 55 r / min for 2.5 min. Then, 0.18 parts of 2-[2-(dimethylamino)ethoxy]ethanol (CAS No.: 1704-62-7) were added and the mixture was mixed at 162°C and 55 r / min for 10.5 min. The mixture was then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
[0043] Fifty parts of recycled high-density polyethylene (HDPE) crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 48°C for 23 min, washed with deionized water for 23 min, filtered, dried at 80°C for 8 h, and then 2.5 parts of amino alcohol modified HDPE, 0.12 parts of antioxidant 1010, 0.12 parts of antioxidant 168 and 0.25 parts of polyethylene wax were added and premixed at 850 r / min for 6 min. The mixture was then fed into a twin-screw extruder and melt-extruded at 175°C. After cooling and pelletizing, modified recycled HDPE masterbatch was obtained.
[0044] Nine parts of linear low-density polyethylene were vacuum dried at 76°C for 6.5 h, and then premixed with 0.16 parts of maleic anhydride, 0.06 parts of vinyltrimethoxysilane, and 0.011 parts of dicumyl peroxide for 23 min. The mixture was then added to a twin-screw extruder and reacted and extruded at 170°C. After cooling and pelletizing, functionalized LLDPE was obtained.
[0045] 2.2 parts of nano-montmorillonite (CAS No.: 1318-93-0) were dried at 95℃ for 2.5 h and cooled to room temperature to obtain dried nano-montmorillonite. 52 parts of high-density polyethylene (PE100), 26 parts of modified recycled HDPE masterbatch, and 8.5 parts of functionalized LLDPE were premixed at 800 r / min for 6 min. Then, 1.6 parts of dried nano-montmorillonite, 8 parts of zinc stearate modified wollastonite fiber, 0.22 parts of antioxidant 1010, 0.22 parts of antioxidant 168, and 0.55 parts of polyethylene wax were added and mixed at 1000 r / min for 8.5 min. The mixture was then melt-extruded at 175℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 h to obtain a modified polyethylene trenchless pipe composite material.
[0046] Example 4 Ten parts of wollastonite fiber were dried at 108℃ for 3.5h, cooled to room temperature, and then 0.35 parts of zinc stearate were added. The mixture was stirred at 1000r / min for 28min and then transferred to a ball mill jar and ball milled at 100r / min for 28min to obtain zinc stearate modified wollastonite fiber.
[0047] 7.2 parts of maleic anhydride-grafted high-density polyethylene were vacuum dried at 82℃ for 11 hours, and then added to a mixer with 0.024 parts of antioxidant 1010. The mixture was heated to 164℃ under nitrogen protection and mixed at 65 r / min for 3.5 min. Then, 0.22 parts of 2-[2-(dimethylamino)ethoxy]ethanol (CAS No.: 1704-62-7) were added and the mixture was further mixed at 164℃ and 65 r / min for 11.5 min. The mixture was then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
[0048] Fifty parts of recycled high-density polyethylene (HDPE) crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 52°C for 28 min, washed with deionized water for 28 min, filtered, dried at 80°C for 8 h, and then 3.5 parts of amino alcohol modified HDPE, 0.18 parts of antioxidant 1010, 0.18 parts of antioxidant 168 and 0.35 parts of polyethylene wax were added and premixed at 950 r / min for 9 min. The mixture was then fed into a twin-screw extruder and melt-extruded at 185°C. After cooling and pelletizing, modified recycled HDPE masterbatch was obtained.
[0049] After vacuum drying 11 parts of linear low-density polyethylene at 79°C for 7.5 h, it was premixed with 0.19 parts of maleic anhydride, 0.09 parts of vinyltrimethoxysilane, and 0.014 parts of dicumyl peroxide for 28 min. The mixture was then added to a twin-screw extruder and reacted and extruded at 175°C. After cooling and pelletizing, functionalized LLDPE was obtained.
[0050] 2.8 parts of nano-montmorillonite (CAS No.: 1318-93-0) were dried at 105℃ for 3.5 h and cooled to room temperature to obtain dried nano-montmorillonite. 58 parts of high-density polyethylene (PE100), 29 parts of modified recycled HDPE masterbatch, and 9.5 parts of functionalized LLDPE were premixed at 800 r / min for 7 min. Then, 1.9 parts of dried nano-montmorillonite, 9.5 parts of zinc stearate modified wollastonite fiber, 0.28 parts of antioxidant 1010, 0.28 parts of antioxidant 168, and 0.65 parts of polyethylene wax were added and mixed at 1000 r / min for 9.5 min. The mixture was then melt-extruded at 185℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 h to obtain a modified polyethylene trenchless pipe composite material.
[0051] Example 5 Ten parts of wollastonite fiber were dried at 110℃ for 4 hours, cooled to room temperature, and then 0.4 parts of zinc stearate were added. The mixture was stirred at 1000 r / min for 30 min, and then transferred to a ball mill jar and ball milled at 100 r / min for 30 min to obtain zinc stearate modified wollastonite fiber.
[0052] 7.5 parts of maleic anhydride-grafted high-density polyethylene were vacuum dried at 85°C for 12 hours. Then, 0.025 parts of antioxidant 1010 were added to a mixer and heated to 165°C under nitrogen protection. The mixture was then mixed at 70 r / min for 4 minutes. 0.25 parts of 2-[2-(dimethylamino)ethoxy]ethanol (CAS No.: 1704-62-7) were added and the mixture was further mixed at 165°C and 70 r / min for 12 minutes. The mixture was then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
[0053] Fifty parts of recycled high-density polyethylene (HDPE) crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 55°C for 30 min, washed with deionized water for 30 min, filtered, dried at 80°C for 8 h, and then 4 parts of amino alcohol modified HDPE, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.4 parts of polyethylene wax were added and premixed at 1000 r / min for 10 min. The mixture was then fed into a twin-screw extruder and melt-extruded at 190°C. After cooling and pelletizing, modified recycled HDPE masterbatch was obtained.
[0054] After vacuum drying 12 parts of linear low-density polyethylene at 80℃ for 8 hours, it was premixed with 0.2 parts of maleic anhydride, 0.1 parts of vinyltrimethoxysilane and 0.015 parts of dicumyl peroxide for 30 minutes, and then added to a twin-screw extruder. The mixture was reacted and extruded at 175℃, cooled and pelletized to obtain functionalized LLDPE.
[0055] Three parts of nano-montmorillonite (CAS No.: 1318-93-0) were dried at 110℃ for 4 hours and cooled to room temperature to obtain dried nano-montmorillonite. 60 parts of high-density polyethylene (PE100), 30 parts of modified recycled HDPE masterbatch, and 10 parts of functionalized LLDPE were premixed at 800 r / min for 8 minutes. Then, 2 parts of dried nano-montmorillonite, 10 parts of zinc stearate modified wollastonite fiber, 0.3 parts of antioxidant 1010, 0.3 parts of antioxidant 168, and 0.7 parts of polyethylene wax were added and mixed at 1000 r / min for 10 minutes. The mixture was then melt-extruded at 190℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 hours to obtain a modified polyethylene trenchless pipe composite material.
[0056] Example 6 Ten parts of wollastonite fiber were dried at 106℃ for 3 hours, cooled to room temperature, and then 0.32 parts of zinc stearate were added. The mixture was stirred at 1000 r / min for 22 min, and then transferred to a ball mill jar and ball milled at 100 r / min for 26 min to obtain zinc stearate modified wollastonite fiber.
[0057] 6.8 parts of maleic anhydride-grafted high-density polyethylene were vacuum dried at 81°C for 10 hours, and then added to a mixer with 0.022 parts of antioxidant 1010. The mixture was heated to 163°C under nitrogen protection and mixed at 60 r / min for 3 minutes. Then, 0.21 parts of 2-[2-(dimethylamino)ethoxy]ethanol (CAS No.: 1704-62-7) were added and the mixture was further mixed at 163°C and 60 r / min for 11 minutes. The mixture was then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
[0058] Fifty parts of recycled high-density polyethylene (HDPE) crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 50°C for 26 min, washed with deionized water for 26 min, filtered, dried at 80°C for 8 h, and then 3.2 parts of amino alcohol modified HDPE, 0.16 parts of antioxidant 1010, 0.16 parts of antioxidant 168 and 0.32 parts of polyethylene wax were added and premixed at 900 r / min for 8 min. The mixture was then fed into a twin-screw extruder and melt-extruded at 182°C. After cooling and pelletizing, modified recycled HDPE masterbatch was obtained.
[0059] 10.5 parts of linear low-density polyethylene were vacuum dried at 78°C for 7 hours, and then premixed with 0.18 parts of maleic anhydride, 0.08 parts of vinyltrimethoxysilane, and 0.013 parts of dicumyl peroxide for 26 minutes. The mixture was then added to a twin-screw extruder and reacted and extruded at 165°C. After cooling and pelletizing, functionalized LLDPE was obtained.
[0060] 2.6 parts of nano-montmorillonite (CAS No.: 1318-93-0) were dried at 102℃ for 3 hours and cooled to room temperature to obtain dried nano-montmorillonite. 56 parts of high-density polyethylene (PE100), 27 parts of modified recycled HDPE masterbatch, and 9.2 parts of functionalized LLDPE were premixed at 800 r / min for 7 minutes. Then, 1.8 parts of dried nano-montmorillonite, 8.8 parts of zinc stearate modified wollastonite fiber, 0.26 parts of antioxidant 1010, 0.26 parts of antioxidant 168, and 0.62 parts of polyethylene wax were added and mixed at 1000 r / min for 9 minutes. The mixture was then melt-extruded at 182℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 hours to obtain a modified polyethylene trenchless pipe composite material.
[0061] The present invention also includes comparative examples and related experiments.
[0062] Comparative Example 1 Compared with Example 1, the only difference is that amino alcohol modified HDPE was not prepared. Instead, recycled HDPE masterbatch was used instead of modified recycled HDPE masterbatch. Specifically, 50 parts of recycled high-density polyethylene crushed material were screened, placed in a 1 wt% sodium carbonate aqueous solution, washed at 50°C for 25 min, washed with deionized water for 25 min, filtered, and dried at 80°C for 8 h to obtain recycled HDPE masterbatch. Other preparation methods and components were completely consistent, and finally, a composite material for trenchless polyethylene pipes was obtained.
[0063] Comparative Example 2 Compared with Example 1, the only difference is that no functionalized LLDPE was added. The other preparation methods and components are completely the same, and a composite material for trenchless polyethylene pipes is finally obtained.
[0064] Comparative Example 3 Compared with Example 1, the only difference is that conventional wollastonite fibers are used instead of zinc stearate modified wollastonite fibers. The other preparation methods and components are completely the same, and a composite material for trenchless polyethylene pipes is finally obtained.
[0065] Performance testing The composite materials obtained in Examples 1-6 and Comparative Examples 1-3 were extruded into pipes to prepare polyethylene pipe samples with the same outer diameter and wall thickness. Tensile yield stress and elongation at break were tested according to GB / T8804.1-2003 "Determination of tensile properties of thermoplastic pipes - Part 1: General test methods", ring stiffness was tested according to GB / T9647-2015 "Determination of ring stiffness of thermoplastic pipes", and notched simply supported beam impact strength was tested according to GB / T1043.1-2008 "Determination of impact properties of simply supported beams of plastics - Part 1: Non-instrumental impact test". The specific performance test results are shown in Table 1.
[0066] Table 1
[0067] As shown in Table 1, the tensile properties, ring stiffness, and impact resistance of Examples 1-6 are all superior to those of Comparative Examples 1-3. Compared with Example 1, Comparative Example 1 did not use amino alcohol-modified HDPE to pre-modify the recycled high-density polyethylene, resulting in a significant decrease in its tensile yield stress, elongation at break, and ring stiffness; Comparative Example 2 did not add functionalized LLDPE, and its notched simply supported beam impact strength decreased to 20.9 kJ / m. 2 The performance of Comparative Example 3 was significantly worse than that of Example 1. Due to the use of conventional wollastonite fibers instead of zinc stearate modified wollastonite fibers, the tensile properties, ring stiffness, and impact resistance of Comparative Example 3 also decreased to some extent.
[0068] To further verify the wear resistance and scratch resistance of the polyethylene trenchless pipe composite material prepared in this invention, the composite materials prepared in Examples 1-6 and Comparative Examples 1-3 were respectively injection molded into standard sheet samples. Tests were conducted according to GB / T3960-2016 "Plastics Sliding Friction and Wear Test Method", and the wear rate was calculated to evaluate the wear resistance. To simulate the frictional effect of hard particles such as sand and rock on the outer wall of the pipe during trenchless towing construction, a sandpaper reciprocating abrasion auxiliary test was conducted: the outer surface of the sample was contacted with 80-mesh silicon carbide sandpaper and rubbed reciprocally 2000 times under a 10N load. The mass loss of the sample before and after the test was measured, and the average groove depth of the wear area was measured using a three-dimensional profilometer to evaluate the wear resistance and scratch resistance of each sample under rough and hard contact conditions. The specific test results are shown in Table 2.
[0069] Table 2
[0070] As shown in Table 2, the wear rate, mass loss rate, and average groove depth of Examples 1-6 were significantly lower than those of Comparative Examples 1-3 in the simulation test, indicating that the composite material prepared by this invention has better wear resistance and scratch resistance under rough and hard contact conditions. Comparative Example 1, which did not use amino alcohol-modified HDPE to pre-modify the recycled high-density polyethylene, had the highest wear rate, mass loss rate, and average groove depth. Comparative Example 2, which did not add functionalized LLDPE, and Comparative Example 3, which used conventional wollastonite fiber, also had a significant impact on the wear rate, mass loss rate, and average groove depth.
[0071] In summary, the composite material obtained by this invention has the properties of strength, toughness, impact resistance, and wear and scratch resistance, and can be applied to polyethylene trenchless pipes.
[0072] The above are preferred embodiments of the present invention. Those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified polyethylene trenchless pipe composite material, characterized in that, Includes the following steps: S1. Maleic anhydride-grafted high-density polyethylene is vacuum dried, then mixed with antioxidant and 2-[2-(dimethylamino)ethoxy]ethanol under inert gas protection, discharged, and granulated to obtain amino alcohol modified HDPE. S2. The recycled high-density polyethylene crushed material is screened, washed, filtered, dried, and then premixed with amino alcohol modified HDPE and additives. It is then melt-extruded and granulated to obtain modified recycled HDPE masterbatch. S3. After vacuum drying of linear low-density polyethylene, it is premixed with maleic anhydride, vinyltrimethoxysilane and dicumyl peroxide, reacted and extruded, and granulated to obtain functionalized LLDPE. S4. High-density polyethylene, modified recycled HDPE masterbatch and functionalized LLDPE are premixed, and then dried nano-montmorillonite, zinc stearate modified wollastonite fiber and other additives are added and mixed. The mixture is then melt-extruded, granulated and vacuum-dried to obtain a modified polyethylene trenchless pipe composite material.
2. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, In step S1, maleic anhydride-grafted high-density polyethylene is vacuum dried at 75-85°C for 8-12 hours, then added to a mixer with an antioxidant, heated to 160-165°C under nitrogen protection, and mixed at 50-70 r / min for 2-4 minutes. Then 2-[2-(dimethylamino)ethoxy]ethanol is added and mixed at 160-165°C and 50-70 r / min for 10-12 minutes. The mixture is then discharged, cooled, and pelletized to obtain amino alcohol modified HDPE.
3. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, The amino alcohol modified HDPE comprises the following raw materials in parts by weight: 6-7.5 parts maleic anhydride-grafted high-density polyethylene, 0.02-0.025 parts antioxidant, and 0.15-0.25 parts 2-[2-(dimethylamino)ethoxy]ethanol.
4. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, In step S2, the recycled high-density polyethylene (HDPE) crushed material is screened, placed in a sodium carbonate aqueous solution, washed at 45-55°C for 20-30 minutes, washed with deionized water for 20-30 minutes, filtered, dried at 80°C for 8 hours, and then premixed with amino alcohol-modified HDPE and additives at 800-1000 r / min for 5-10 minutes. The mixture is then fed into a twin-screw extruder and melt-extruded at 170-190°C. After cooling and pelletizing, modified recycled HDPE masterbatch is obtained. The mass ratio of the recycled HDPE crushed material to the amino alcohol-modified HDPE is 50:(2-4).
5. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 4, characterized in that, The concentration of the sodium carbonate aqueous solution is 1 wt%; the additives include 0.1-0.2 parts of antioxidant 1010, 0.1-0.2 parts of antioxidant 168 and 0.2-0.4 parts of polyethylene wax.
6. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, In step S3, linear low-density polyethylene is vacuum dried at 75-80°C for 6-8 hours, then premixed with maleic anhydride, vinyltrimethoxysilane, and dicumyl peroxide for 20-30 minutes, added to a twin-screw extruder, reacted and extruded at 160-175°C, cooled, and pelletized to obtain functionalized LLDPE.
7. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, The functionalized LLDPE comprises the following raw materials in parts by weight: 8-12 parts linear low-density polyethylene, 0.15-0.2 parts maleic anhydride, 0.05-0.1 parts vinyltrimethoxysilane, and 0.01-0.015 parts dicumyl peroxide.
8. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, The zinc stearate modified wollastonite fiber is obtained by drying wollastonite fiber at 100~110℃ for 2~4h, cooling it to room temperature, adding zinc stearate, mixing and stirring at 1000r / min for 15~30min, and then transferring it to a ball mill jar and ball milling at 100r / min for 20~30min; the mass ratio of wollastonite fiber to zinc stearate is 10:(0.2~0.4). The dried nano-montmorillonite is obtained by drying nano-montmorillonite at 90~110℃ for 2~4h and then cooling it to room temperature.
9. The method for preparing a modified polyethylene trenchless pipe composite material according to claim 1, characterized in that, In step S4, high-density polyethylene, modified recycled HDPE masterbatch, and functionalized LLDPE are premixed at 800 r / min for 5-8 min, then dried nano-montmorillonite, zinc stearate modified wollastonite fiber, and other additives are added and mixed at 1000 r / min for 8-10 min. The mixture is then melt-extruded at 170-190℃, cooled, pelletized, and vacuum-dried at 70℃ for 5 h to obtain a modified polyethylene trenchless pipe composite material. The other additives are 0.2-0.3 parts of antioxidant 1010, 0.2-0.3 parts of antioxidant 168, and 0.5-0.7 parts of polyethylene wax.
10. A composite material for modified polyethylene trenchless pipes, characterized in that, The modified polyethylene trenchless pipe composite material is prepared using the preparation method according to any one of claims 1 to 9, comprising the following raw materials in parts by weight: 50 to 60 parts high-density polyethylene, 25 to 30 parts modified recycled HDPE masterbatch, 8 to 10 parts functionalized LLDPE, 1.5 to 2 parts dried nano-montmorillonite, 7 to 10 parts zinc stearate modified wollastonite fiber, and 0.9 to 1.3 parts other additives.
Citation Information
Patent Citations
Polyethylene pipe for trenchless engineering
CN114181444A
Insulating material for electric power system and application thereof
CN104130503A
Cable for automobile manufacture
CN106611631A